Competing hydrogen-bond and halogen-bond donors in crystal engineering - Aakeröy, Christer B.; Panikkattu, Sheelu; Chopade, Prashant D.; Desper, John (My University, 2012)
In order to study the structure-directing competition between hydrogen- and alogen-bond donors we have synthesized two ligands, 3,3’-azobipyridine and 4,4’-azobipyridine, and co-crystallized them with a series of bi-functional donor molecules comprising an activated halogen-bond donor (I or Br) as well as a hydrogen-bond donor (acid, phenol or oxime) on the same backbone. Based on the subsequent single-crystal analysis, 5 of 6 co-crystals of 3,3’-azobipyridine are assembled using hydrogen bonds as the primary driving force accompanied by weaker secondary (C-X...O) interactions. However, in 5 out of the 6 co-crystals of 4,4’-azobipyridine, both hydrogen bonds (O-H...N) and halogen bonds (C-X...N) are present as structure-directing interactions leading to 1-D chains. Since the charges on the acceptor sites in 3,3’-and 4,4’-azobipyridine are very similar, the observed difference in binding behaviour highlights the importance of binding-site location on the acceptor molecules (anti-parallel in 3,3’-azobipyridine and co-linear in 4,4’-azobipyridine) as a direct influence over the structural balance between hydrogen- and halogen-bond donors.
Keywords: Hydrogen-bond; Halogen-bond; Crystal engineering; Supramolecular chemistry; Azopyridines